ANALISIS POTENSI EKONOMI KABUPATEN BANYUWANGI - Ahmad Afan Ayubi (Jurnal Ekonomi Pembangunan, 2014)
The purpose of this study was to identify sectors of potential economic, competitive competitive, comparative and specialization, to then be used as a driver of economic growth and development of the district of Banyuwangi. This type of research is descriptive quantitative research. The data used in this research is secondary data and time series. These results indicate that by Location Quotient (LQ), the sector identified as a leading sector is agriculture. Based on the average results of analysis Growth Ratio Method (MRP), shows found their economic sectors that stand at both district and provincial Banyuwangi East Java, with the construction sector and the sectors of trade, hotel and restaurant.